Calcium-induced conidiation in Penicillium cyclopium: calcium triggers cytosolic alkalinization at the hyphal tip. - Roncal, T (1993)
Addition of Ca2+ (1 to 10 mM) to submerged cultures of Penicillium cyclopium induces conidiation. Ca2+ induced an increase in cytosolic pH from approximately 7.00 to > 7.60 in less than 10 min, as determined with the fluorescent pH probe fluorescein. Measurement of the H(+)-ATPase activity in total membrane fractions did not show any stable activation in vivo as a result of Ca2+ treatment. By fluorescence ratio imaging microscopy, it was observed that vegetative hyphae exhibit a tip-to-base pH gradient, with the tip being more acidic. Ca2+ caused this gradient to dissipate within 10 min. The effect of several agents that are supposed to cause internal acidification, by different means, on conidiation was tested. Concentrations of these agents that did not significantly affect growth but inhibited Ca(2+)-induced conidiation also prevented the intracellular alkalinization observed after exposure to the cation. Calcium channel blockers (lanthanum, cobalt, verapamil, and nifedipine) were not able to inhibit Ca(2+)-induced conidiation, although their effect on calcium uptake was not evaluated. However, the combined results point towards externally bound Ca2+ as the primary agent of conidiation induction, causing changes in plasma membrane function which disrupt the pH gradient observed during apical growth.